Record of short-lived “orogen” on Eurasian continental margin by South China Sea obduction preserved in Taiwan collision - Lo, Yun-Chieh; Chen, Chih-Tung; Lo, Ching-Hua; Chung, Sun-Lin; Yeh, Meng-Wan (Frontiers in Earth Science, 2023)
The Taiwan mountain belt results from arc-continent collision following total subduction of South China Sea and subsequent Luzon forearc closure, a process important in accretionary growth of continents. Due to the oblique convergence, the southern tip of the Taiwan Island is experiencing incipient collision and is key to observe the oceanic-continental subduction transition. Within the monotonous turbidite extensively exposed on the Hengchun Peninsula as uplifted Manila Trench accretionary wedge, the Shihmen Conglomerate as a few intercalated lenses of coarse mafic pebbles represents a dramatic change in sediment provenance and the causal tectonic event. New zircon U-Pb and amphibole 40Ar/39Ar ages are acquired from the sediments including sands and mafic pebbles which are either gabbro or foliated amphibolite. The 22-24 Ma zircon crystallization ages confirm the South China Sea origin of the mafic clasts, while the much-younger 13 ± 2 Ma amphibole 40Ar/39Ar isochron ages from foliated amphibolites suggest a later thermal-tectonic event other than seafloor metamorphism. The amphibole 40Ar/39Ar ages overlap with the biostratigraphic age (~11-14 Ma) indicate the mafic source rocks were exhumed and eroded in a high-relief topography right after being metamorphosed. Detrital zircon U-Pb ages from a sandy layer within the conglomerate are also mostly identical to those from the mafic pebbles. Since the paleo-current of the Shihmen Conglomerate was similar to the neighboring turbidites which were sourced from major rivers draining southeast Chinese continent, the provenance of the mafic pebbles and sands was best explained as an isolated subaerial mountain on the Eurasian continental margin, which had very limited temporal and spatial extent as the detritus products are scarcely distributed. The most likely cause of the ephemeral mountain was South China Sea obduction onto the Eurasian continental margin when the latter initially impinged the Philippine Sea Plate at the Manila Trench, where the gabbroic oceanic crust was uplifted and exhumed subsequent to being dynamically metamorphosed along the basal thrust.